Sistem Informasi Produksi Komuditas Sawit Pada PT. Dharmasraya Palma Sejahtera - Syaputra, Dikky; Sharipuddin, Sharipuddin (Jurnal Manajemen Sistem Informasi, 2023)
Production information system at PT. Dharmasraya Palma Sejahtera is still manually using paper and inputted into Microsoft Word and Excel, so there are problems in recording and reporting. Difficulties in the process of making reports and reporting will increase because the storage media is only in the form of archived document files. Based on the existing problems, a production information system design is needed that can help solve the problem. The purpose of this research is to analyze and design an information system for palm oil commodity production by applying the SCRUM framework. The method used in this research is the SCRUM framework which consists of 3 stages, namely (1) Product Backlog, (2) Sprint Backlog, (3) Product Complete. This study uses modeling tools in the form of Usecase diagrams, Activity diagrams, and class diagrams. The results of this study are a prototype of an information system for the production of palm oil commodities with a design using the SCRUM framework.